(untitled) (Journal of Hama University, 2021)
This study aimed to define the role of social responsibility in its dimensions (economic dimension, ethical dimension, human dimension) in improving the quality of health services in Al Noor Specialist Hospital. The researcher relied on the deductive approach, and relied on the descriptive approach to characterizing the research variables and analyzing them based on the initial data that was collected, where she conducted a field study on Al Noor Specialized Hospital to collect the necessary preliminary data, and the variables were measured on all the primary data collected through the following. Designed by informing the researcher of previous studies and literature, and in order to test the hypotheses, the researcher dumped the primary data in a database that was analyzed using SPSS version / 20 /. The study concluded that there is an association between social responsibility in its various dimensions and the improvement of the quality of the health service in the organization under study, and the hospital did not succeed in maintaining the level of quality and the measures taken to address the Corona virus, due to its inability to succeed in adopting methods of prevention and precaution from the point of view of the sample members .